Psikoterapi Pemberdayaan: Berbagi Tiga Hal Baik untuk Mengatasi Burnout Perawat di Era COVID-19 - Sri Nining; Rr. Tutik Sri Hariyati; La Ode Abdul Rahman; Lilis Rayatin (Journal of Telenursing (JOTING), 2021)
This study aims to identify problems and determine improvement strategies to overcome burnout nurses. The research method used is a case report to assess quality improvement with an 8-step approach to change starting from problems with observation and screening of burnout using the Maslach Burnout Inventory Human Services Survey (MBI-HSS), analysis using a fishbone approach, determining improvement strategies, implementing and program evaluation. The results showed that 55% of nurses experienced a decrease in self-esteem, but through the Empowerment Psychotherapy program: Three Good Things, which was carried out for two weeks, it was able to reduce the burnout level of nurses as assessed by the Mini Z burnout survey. In conclusion, Empowerment Psychotherapy: Three Good Things can overcome nurse burnout problems. It is recommended that the implementation of this program be carried out thoroughly in all work units. Keywords: Burnout Management, Nurses, Empowerment Psychotherapy, Three Good Things